The educational policies of The Soviet Union and its impact on the well-being of The Soviet Muslims - Akhmetova, Elmira (2018)
This paper elaborates the educational policies adopted by the Soviet Union and how these policies negatively affected the well-being of Muslims living under the Soviet Union.